In vitro antioxidant of the protein hydrolysate isolated from the seeds of hoary basil (Ocimum basilicum) - Semanit, Karittha; Piapukiew, Jittra; Noitang, Sajee; Karnchanatat, Aphichart (Food and Applied Bioscience Journal, 2017)
Oxidation plays an important role in the basic processes of life, such as the production of energy and phagocytises employed by the immune system. However, when an imbalance between oxidants and antioxidants exists in vivo, oxidation can become uncontrolled and result in diseases such as arthritis, cancer, atherosclerosis, and Alzheimer’s disease. The objective of this research work to produce hoary basil seed protein hydrolysates (HBPs) and their peptides with antioxidant properties. Enzymatic hydrolysis of the seeds was performed by using a bacterial alkaline protease, Protease G6 at their optimal conditions. The degree of hydrolysis of HBPs with Protease G6 hydrolysis and DPPH radical scavenging assay, IC50 values showed 55.134±0.10% and 0.0196±0.064 μg/mL for 270 min. These results show that HBPs increased the degree of hydrolysis and antioxidant activity of protein hydrolysates. HBPs were fractionated into three fractions, HBPs-I (MW>10 kDa), HBPs-II (MW = 5–10 kDa), and HBPs-III (MW<5 kDa) and the in vitro antioxidant activities of all fractions were determined. HBPs-III showed the lowest IC50 value at 0.02523±0.14 μg/mL for DPPH radical scavenging activity. The findings suggest the importance of hoary basil seed protein as a source of bioactive peptides.